2016
DOI: 10.1042/bsr20160054
|View full text |Cite
|
Sign up to set email alerts
|

ATP increases the migration of microglia across the brain endothelial cell monolayer

Abstract: To elucidate the mechanism of microglial migration across the blood–brain barrier (BBB), we developed an in vitro co-culture system and analysed real-time BBB integrity during transmigration. We show that ATP promotes microglia transmigration via a mechanism involving microglial matrix metalloproteinases (MMPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…MMPs, and specifically MMP‐2, play a role in microglia migration and chemotaxis . MMP activation may facilitate microglia migration toward the tumor and may also be important for tumor invasion.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs, and specifically MMP‐2, play a role in microglia migration and chemotaxis . MMP activation may facilitate microglia migration toward the tumor and may also be important for tumor invasion.…”
Section: Resultsmentioning
confidence: 99%
“…However, we note that the calcium levels measured in our study could also be sensitive to the culture conditions including the presence of electrospun fibers, ATP dosage and the use of the same substrates for measuring calcium responses before and after ATP addition. Further, although an ATP dose between 1 and 10 µM is known to induce microglia migration within a timeframe of 3–48 hr (Lambert, Ase, Séguéla, & Antel, 2010; Maeda et al, 2016), cell migration was not observed in our study within the short time‐period of 6–7 min that was used for imaging. The focus of the present study was to develop an imaging approach to monitor the effect of ATP treatment through intracellular calcium imaging on electrospun matrices (after 5 min of ATP addition).…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have suggested that matrix metalloproteinases (MMPs) play important roles in regulating microglial migration. ATP, speci cally, induces microglial migration by regulating MMP2 and MMP9 [53,80]. Furthermore, MMP2, MMP9, MMP12, and MMP14 have all been found to be increased in LPS-mediated microglial migration [78,81].…”
Section: Discussionmentioning
confidence: 99%